International rice trade and security stocks: Prospects for an expanded Asian international rice reserve - Dorosh, Paul A.; Childs, Abigail (International Food Policy Research Institute, 2014)
This paper examines the recent experience with international rice reserves in Asia and re-examines the roles of national stocks and international trade in stabilizing domestic rice prices and availability in importing countries.